Computer-Based Information Systems for Management: A Survey (Book). - Sterling, Robert R.; Radosevich, Raymond (The Accounting Review, 1970)
Reviews the book "Computer-Based Information Systems for Management: A Survey," by Neil C. Churchill, John H. Kempster and Myron Uretsky.